Comparison of Vertical and Horizontal Facial Ratio–An Anthropometric Study - Sadacharan, Chakravarthy Marx (The Journal of Dentists, 2016)
Introduction: Information on facial ratios of men and women has significant application in science and clinical practice. Facial proportions differ from one individual to another within a gender, group and race. Data on facial anthropometric ratios for men may not generally be appropriate for women of identical ethnicities. Objectives: The aim was to determine the difference in the facial ratios among Indian American men and women, and compare these results with facial ratios of Indian and Caucasian persons. Methods: Using a digital caliper, direct facial measurements of 200 Indian American students (100 men and 100 women) were made. These were students of American University of Antigua (AUA), Antigua, ages 18-30 years. Facial ratios amongst this group were then calculated and the differences between sexes compared. Results: The mandibulo-lower facial height, upper face-face height, mandibulo-facial height, mandibulo-upper face height, eye fissure-nasal width, upper lip-nose height, mandibular and upper lip height-mouth width ratios showed sexual differences, which were extremely statistically significant (p<0.001). Horizontal to horizontal facial ratios did not show statistically significant sexual difference when compared with vertical to vertical and vertical to horizontal facial ratios in between sexes. Conclusion: Among Indian and Caucasian populations, the vertical to horizontal facial ratios showed significant sexual differences. The present study variance in the facial ratios amid Indian American sexes can be clinically applied by surgeons during procedures involving the face to help in achieving an attractive and symmetrical appearance.